FACEBOOK SEBAGAI MEDIA PEMBELAJARAN YANG INOVATIF, INTERAKTIF, DAN KOMUNIKATIF DI DALAM PENGEMBANGAN KUALITAS PEMBELAJARAN - Ino Angga Putra (EDUSCOPE: Jurnal Pendidikan, Pembelajaran, dan Teknologi, 2016)
ABSTRACTDevelopments in the world of education experienced a fairly complex problem where one of them the quality of learning. It should be noted and followed up by adjusting the era of the all-powerful state through the development of technology, information and communication (ICTs). Utilization of ICT through the internet facility in learning activities can improve the quality of learning both in the classroom and outside the classroom. One effort to improve the quality of learning is the learning activities with the Internet is a form of E-learning by using the facebook application. Facebook is a media that is already known to many people and can be operated anywhere and anytime. The use of media facebook expected to improve student learning outcomes. The discussion will be directed to the use of Facebook as a medium of learning an innovative, interactive, and communicative in improving the quality of the learning process. KEYWORDS: facebook, media of learning, the quality of learning